PMO-207 Changing trends in upper and lower gastrointestinal bleeding over a 13-years period. (28th May 2012) - Smith, C; Thomson, J M; Fraser, A; Vijayan, B; Leeds, J S
Abstract : Introduction: Acute gastrointestinal (GI) bleeding is a common medical emergency associated with significant mortality and morbidity. Recent studies suggest that the incidence of upper GI bleeding (UGIB) has decreased mainly due to reduction in peptic ulcer disease. Trends for lower GI bleeding (LGIB) are less well defined and therefore the burden on health services is unknown. The aim of this study was to examine the trends in all types of GI bleeding presenting to our bleeding unit over a 13-year period. Methods: Our Gastrointestinal Bleeding Unit opened in October 1991 and serves a population of around 600 000. The unit admits patients with both upper (UGIB) and lower (LGIB) bleeding and maintains a prospective database of all admissions. The database was analysed for yearly admissions over the period 1991–2004 with respect to total number of admissions and then stratified by bleeding source, age, gender and diagnosis. Age, gender, bleeding source and disease specific rates were calculated. Results: 12 572 patients (median age 66, 7028 males) were admitted to the unit over the period October 1991–October 2004. 9544 presented with symptoms of UGIB and 2508 with symptoms of LGIB with 520 patients being unclassified due to a mixture of symptoms. Overall numbers of admissions increased from 728 in the first year to 1003 in year six then reached a plateau thereafter around 950 per year. Overall 30-day mortality was 9.7% (8.7–10.8) for UGIB and 11.4% (9.2–14.1) for LGIB and there was no change in rebleeding rates. Median age increased significantly from 64 years to 68 years (p<0.001) over this period mirrored by increasing age in UGIB (63 to 65 years, p<0.001) but no significant difference in LGIB. Patients presenting with LGIB were significantly older than those presenting with UGIB (70 vs 64, p<0.001) and were more likely to be female (OR 1.64, 95% CI 1.5 to 1.8, p<0.001). With respect to UGIB, there was a non significant increase in admissions overall but there was a rise in variceal bleeding (OR 2.5, 95% CI 1.5 to 4.4, p=0.005) but a reduction in bleeding peptic ulcers (OR 0.65, 95% CI 0.49 to 0.87, p=0.039) particularly in males age <40 years. There was a significant increase in the numbers of admission due to LGIB (p<0.001) predominantly due to inflammatory bowel disease (p=0.04), haemorrhoidal bleeding (p=0.001) and ischaemic colitis (p=0.0016). Conclusion: There has been an increase in numbers of patients admitted with GI bleeding and this population is significantly older over time. There has been a decline in peptic ulcer bleeding but a rise in variceal cases. Admissions overall for GI bleeding have increased mainly due to a significant rise in LGIB mainly accounted for by IBD, haemorrhoids and ischaemic colitis. Competing interests: None declared.